A Critical Review of the Activity-Based Learning Model in Teaching Arabic Writing to AFL Learners: A Montessori-Informed Perspective - Wahyu Hanafi Putra; Thoyyibah, Anisatu (Al-Himam, 2025)
This study critically evaluates the implementation of the Activity-Based Learning (ABL) model in teaching Arabic paragraph writing to Arabic as a Foreign Language (AFL) students, as presented in the work of Sathikulameen et al. (2023) published in Ijaz Arabi. Adopting a qualitative library research approach, this study analyzes previously published materials, focusing on the ten-stage ABL writing framework used at The New College, Chennai, India. Data were obtained through document analysis and examined using interpretive content analysis to assess the instructional and pedagogical design. Three key critiques emerge from the Montessori perspective. First, the model overlooks psycholinguistic foundations by failing to prioritize vocabulary comprehension. Second, the linear writing process lacks sufficient repetition, a core component for skill acquisition. Third, the ABL approach restricts student autonomy in idea development and topic selection, contrary to Montessori principles of learner independence. The study concludes that the ABL model should be revised by integrating Montessori-informed practices to promote a more student-centered and developmentally appropriate approach to Arabic writing instruction for AFL learners.